Determining the photocatalytic effect of photocatalytic composite by utilizing the loading of TiO2 to CaCO3 from Baluko shell (Atrina pectinata) - Profeta, Angelo Gabriel P (Animo Repository, 2023)
This study investigates the photocatalytic efficiency of a novel composite material by loading TiO2 onto CaCO3 derived from baluko shells (Atrina pectinata). The composites were synthesized with varying mass ratios of TiO2 to CaCO3 and characterized for their photodegradation capabilities using Rhodamine B (RhB) and Methylene Blue (MB) as model organic dyes. The highest photodegradation efficiency, reaching 64.1% for RhB in just 60 minutes, was observed in the 10% TiO2-CaCO3 composite. Kinetic studies revealed a pseudo first-order reaction, with rate constants inversely related to the mass ratios of the composites. Comparative analyses with individual components (TiO2 Anatase and CaCO3) demonstrated the superior performance of the composite in degrading both RhB and MB. Recycling experiments showcased the stable performance of the 10% TiO2-CaCO3 composite over three cycles. Morphological and elemental analyses confirmed the successful incorporation of CaCO3 and highlighted structural changes in the composite, contributing to its enhanced photocatalytic activity. The study provides valuable insights into the development of an efficient and recyclable photocatalyst for potential applications in wastewater treatment.